Evaluation of the impact caused by boll weevil in the infested area of Campinas and Sorocaba, São Paulo State, in the 83/84 season - Campanhola, Clayton; Martin, Dial Franklin; Schattan, Salomão (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this investigation was to evaluate the damage caused by the boll weevil and other pests that attack squares and bolls of cotton as well as controls used by growers in the boll weevil (Anthonomus grandis Boheman, 1843) infested area of São Paulo State, throughout the 1983/84 season. A survey was conducted in a random sample of farms in municipalities infested by the boll weevil in the Campinas and Sorocaba regions. There was a decrease of 19.9% and 32.9%, respectively, in the planting of cotton in the two regions during the 83/84 season as compared with the previous season. However in the 83/84 crop there was an increase in cotton yield per hectare of 26.8% and 29.9% in the Campinas and Sorocaba regions, respectively. The average number of spray applications increased from 2.8 to 4.1 in the 83/84 season over 82/83. Insecticides in descending order of use were: methyl parathion, endosulfan, endrin and monocrotophos. The losses on farms with the highest boll weevil damage was 4.7% in the Campinas region and 6.6% in the Sorocaba region. In the 83/84 crop the boll weevil caused more damage than pink bollworm, expressive pest in the region.
Keywords: Anthonomus grandis; survey; losses; economic importance; spraying costs